Memantik Keputusan Pembelian Ulang Jasa Wisata dan Faktor Pengaruhnya (Studi kasus Wisatawan Di Kebun Binatang Mangkang Semarang) - Rahayu, Rina Mukti (Jurnal Riptek, 2024)
The research objective is to analyze the impact of ticket prices and service quality on the decision to repurchase tourism services at the Mangkang Zoo, Semarang. This research uses IBM SPSS version 25 regression analysis. Accidental sampling technique was used to take a sample of 100 respondents. The results of this research show that ticket prices and service quality have a positive and significant effect on the decision to repurchase tourism services at the Mangkang Zoo, Semarang. This study can be used as reference material for managers of the Mangkang Zoo in Semarang to design and establish effective and efficient marketing policies. The results of this study also contribute to the development of knowledge and input for the Mangkang Zoo in Semarang to focus more on developing the performance facilities of the Mangkang Zoo in Semarang